Contracting the Void: Land, Capital, and Sequestration - Lewis, Madeleine; Righetti, Tara (Columbia Journal of Environmental Law, 2025)
Carbon capture and sequestration (CCS) is poised to play a critical role in efforts to mitigate climate change. As CCS projects proliferate across the United States, they are fundamentally recasting the nature of certain property rights in the subsurface. This has given rise to novel legal and economic questions regarding the acquisition and valuation of pore space for long-term carbon dioxide (CO2) storage. This article examines the emerging legal frameworks and market dynamics for transactions of pore space for geologic carbon sequestration, contributing both a theoretical and uniquely empirical perspective on early transactional models and impacts to the long-term development of the CCS industry. This article offers the first empirical assessment of compensation structures in pore space contracts. Analyzing structures from publicly available agreements, it reveals how project developers and landowners are allocating risk and value at different stages of project development. This illustrates how uncertainties associated with the extent of the subsurface resource, revenue sources, and the timing of development impact deal structure. This has led to emerging trends such as phased bonus payments, dynamic rental structures, and volumetric compensation mechanisms. The structure of these contracts incorporates aspects of other depletable resource contracts, such as oil and gas leases. Carbon sequestration, however, requires greater commonality of pore space resources to assure adequate storage capacity and manage environmental and containment risks. This can require tremendous amounts of land and coordinated operations within the project area. These differences, along with the vital role of carbon removal to climate mitigation, provide an opportunity to critically explore the choice to develop carbon sequestration projects using the same models adopted for oil and gas. Land acquisition adds cost and complexity to these projects. Moreover, landowners may defer leasing until markets are more developed or subsurface resources are more fully characterized, increasing the ultimate cost of climate mitigation. While states have endeavored to reduce transactions costs through legislation, the combination of property law and political choices regarding the development of CCS projects may ultimately impede the timely achievement of climate mitigation as a public good.